In Vivo Evaluation of the Treatment Outcome of Pulpotomy in Primary Molars Using Diode Laser, Formocresol, and Ferric Sulphate - DURMUŞ, BAŞAK (MARY ANN LIEBERT, INC, 2014)
Objective: The purpose of this study was to assess whether the diode laser (DL) pulpotomy method is a suitable alternative to formocresol (FC) and ferric sulphate (FS) pulpotomies in human primary teeth. Background data: Pulpotomy is the amputation of infected coronal pulp to maintain radicular pulp vitality and function. Although FC is regarded as the gold standard for pulpotomy in primary teeth, concerns about its safety have been reported. Lasers are an effective nonpharmacological alternative for treating pulp in children. Methods: This study included 120 primary molars in 58 children 5-9 years of age who underwent an identical conventional pulpotomy technique; the molars were allocated to FC, FS, and DL groups. After removal of the coronal tissue, complete hemostasis of the remaining pulp in the DL group was achieved by DL at 1.5 W, 30 Hz, and 50 mJ, with a 10 sec exposure time. For the FC group, diluted FC (1:5 Buckley's formocresol) was used for 5 min., and for the FS group, a 15.5% FS solution was used for 15 sec. Treatments in all groups were completed with stainless steel crowns and monitored clinically and radiographically at 1, 3, 6, 9, and 12 months. Results: The clinical success rates at 12 months were 97%, 95%, and 100%, whereas the radiographic success rates were 87%, 79%, and 75%, for the FC, FS and DL groups, respectively. The differences in the results were not statistically significant according to the chi(2) test (p > 0.05). Conclusions: DL pulpotomy offers a high clinical success rate, however considering radiographic success rate, it may not replace traditional FC and FS pulpotomies in primary molars.
Keywords: MINERAL TRIOXIDE AGGREGATE; PRIMARY TEETH; CALCIUM HYDROXIDE; PULP THERAPY; GLUTARALDEHYDE